1987
DOI: 10.1007/bf00183845
|View full text |Cite
|
Sign up to set email alerts
|

Acidification effects on larval striped bass, Morone saxatilis in Chesapeake Bay tributaries: A review

Abstract: Reduced striped bass populations along the East Coast of the United States have prompted numerous studies to assess various factors contributing to the decline. Available data from in-situ, on-site and laboratory studies with striped bass in conjunction with water quality and contaminants data confirm that the eastern shore rivers of the Chesapeake Bay (Choptank, Nanticoke, and Pocomoke Rivers) are susceptible to acidic conditions. The Choptank and Nanticoke Rivers are significant striped bass spawning areas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…River flow during the postlarval period and rainfall during the early postlarval period were significantly correlated with each other (P < 0.05, r = 0.80). Rainfall obviously affects river flow and also is associated with acidic, potentially toxic, conditions in at least some striped bass spawning sites in the Chesapeake Bay area, including the Choptank River (Hall 1987). Minimum water temperature during the peak spawning period and rainfall during the early postlarval period were not significantly correlated with one another (P < 0.36, r = -0.48).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…River flow during the postlarval period and rainfall during the early postlarval period were significantly correlated with each other (P < 0.05, r = 0.80). Rainfall obviously affects river flow and also is associated with acidic, potentially toxic, conditions in at least some striped bass spawning sites in the Chesapeake Bay area, including the Choptank River (Hall 1987). Minimum water temperature during the peak spawning period and rainfall during the early postlarval period were not significantly correlated with one another (P < 0.36, r = -0.48).…”
Section: Discussionmentioning
confidence: 96%
“…The combination of acidic precipitation, acidic soils, and low-buffering capacity of surface waters create acidic conditions in coastal plain spawning areas such as the Choptank River (Hall 1987). Increased metal solubility at low pH enhances water toxicity to early life stages of fish (Peterson et al 1982) and striped bass in particular .…”
Section: Discussionmentioning
confidence: 99%
“…A combination of these techniques would assist in the identification of potential threats to the estuarine biota, especially the fishes. Although most current indices depend on juvenile and adult stock information, the increasing data on larval fish dynamics in estuaries (Hall, 1987) bodes well for future ecological and environmental health indices.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%
“…Prior studies have indicated a number of possible factors that influence and, in some cases, may determine larval survival in Morone. Striped bass larvae are affected directly by temperature (Dey 1981: Morgan andRasin 1982;Borcman 1983;Uphoff 1989;Rutherford and Houdc 1995;Secor and Houde 1995), salinity (Turner and Parley 1971;Morgan et al 1981), and dissolved oxygen (Turner and Parley 1971), as well as contaminants and low-pH events (Hall et al 1985;Hall 1987;Uphoff 1989). Temperature has also been implicated in survival of white perch eggs and larvae (Morgan and Rasin 1982;Margulies 1989).…”
mentioning
confidence: 99%